PERNIKAHAN DINI DI INDONESIA - Noviyanti Soleman; Rifki Elindawati (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2019)
Child marriage is one of the big problems occur in the world. It has been set up in Millenium Development Goals, either Sustainable Development Goals point 5. Almost every country in the world face the same problem, as well as Indonesia. Indonesia is among the 10 countries with the largest number in aged 20-24 married before 18 years old. Otherwise, Indonesian law has regulated about child marriage in Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinian, however the number is still high. This research aims to know the level of child marriage in Indonesia and the causes.